Total polyphenols from Syzygium cumini (L.) Skeels fruit extract - Migliato, Ketylin Fernanda [UNESP]; de Carvalho, Elisangela Simoes [UNESP]; Silva do Sacramento, Luis Vitor [UNESP]; Palazzo de Mello, Joao Carlos; Baby, Andre Rolim; Robles Velasco, Maria Valeria; Salgado, Hérida Regina Nunes [UNESP] (Universidade de São Paulo (USP), Conjunto Quimicas, 2009)
A precise, accurate and low cost spectrophotometric method was developed and validated for routine determination of total polyphenols, as pyrogallic acid equivalents, from the percolated and lyophilized extract of Syzygium cumini (L.) Skeels fruits. Validation was assessed experimentally and data were rigorously treated by statistical analysis. Analytical parameters were: linearity, interval (range), precision and recovery/accuracy, limit of detection (LOD, mu g mL(-1)) and limit of quantification (LOQ, mu g mL(-1)). The visible spectrophotometric method presented linearity (r(2) = 0.9979 +/- 0.0010) over the concentration range 0.25-7.5 mu g mL(-1) of standard pyrogallic acid, precision <= 2.918171%, recovery/accuracy ranging from 96.228693 to 107.17701%, LOD = 0.21 mu g mL(-1) and LOQ = 0.64 mu g mL(-1).

Um método espectrofotométrico preciso, rigoroso e de baixo custo foi desenvolvido e validado para a determinação de polifenóis totais, utilizando-se como padrão o ácido pirogálico. O extrato dos frutos de Syzygium cumini (L.) Skeels foi preparado empregando-se o método de percolação com posterior liofilização. A validação foi executada experimentalmente e os dados foram submetidos à análise estatística. Os parâmetros analíticos considerados foram: linearidade, intervalos de precisão e de recuperação, limite de detecção (LD, μg.mL-1) e o limite de quantificação (LQ, μg.mL-1). O método espectrofotométrico apresentou linearidade (r2 = 0,9979 + 0,0010) ao longo do intervalo de concentração de 0,25-7,5 μg mL-1 de ácido pirogálico, padrão de precisão menor do que 2,918171%; recuperação/precisão entre 96,228693 a 107,17701%, e LD = 0,21 μg-mL-1 e LOQ = 0,64 μg mL-1.